Mirrors in the Text: Amélie Nothomb’s Mercure - Lisa F. Signori (Studies in 20th & 21st Century Literature, 2013)
In Belgian author Amélie Nothomb’s 1998 novel Mercure, the multitudes of physical, figurative, and narrative mirrors invite a reflexive reading of the text. While numerous critics have focused on the intertextuality in Mercure—its most obvious manifestation of reflexivity—the novel’s intratextuality has not been analyzed as extensively, and none of these manifestations has been analyzed specifically as an instance of narrative reflexivity. Guided by the theme of mirrors and mirroring, the purpose of this article is to recast in terms of narrative reflexivity some of the extant critical analysis of Mercure, to uncover other as yet unexplored realizations of reflexivity, and to bring them together in a cogent system.
Keywords: Amélie Nothomb; Mercure; mirrors; mirror; mirroring; intertextuality; reflexivity